Transforming Industrial Operations with Blockchain: The Healthcare Application Health Chain - Haziah, Sa’ari; Mohd Rushidi, Mohd Amin; Mohd Saleh, Abbas; Albert Feisal, Ismail; Asmaul Husna, Haris Fadzilah; Mohd Norazmi, Nordin (2023)
Globally, effective application of cloud technology, mobile, social media, analytics, and IoT (Internet of Things), has resulted in new creative products, tight consumer interactions, and enhanced corporate operations. Block-chain technology is reshaping the digital landscape by offering a fresh perspective on efficiency, system security and resilience. Despite its initial popularity as a foundation for digital money, Blockchain is much more than that. It offers a safe way to conduct any form of product or service trade. Growing laws, cybercrime, and fraud are impeding industrial progress even while trusted connections are becoming more and more crucial for growth. To overcome these obstacles, Block-chain will enable more flexible better customer interactions, cloud technology, value chains, quicker product developments, and quicker IoT and integration. Further Block-chain reduces the charge of commerce by providing a reliable bond that is handled devoid of outside interference from parties that might not directly provide value. It is now feasible to create engagements, smart contracts, and agreements with solid cyber-security components built in. In order to show and illustrate the usage of Block-chain technology across numerous industrial applications, this research attempts to build the framework for that. The IBM Block-chain project is used to define and develop the healthcare application Health-chain. The ideas may be used to a variety of trades, including as manufacturing, banking, and government, where scalability, safety, and efficiency are needed. Keywords—Block-chain Technology; Bitcoin; Cloud computing; Control Systems; Cyber-security; Dev-Ops; IBM; Cybercrime; Health-chain; Internet of things